Exploring self-care abilities among women in prisons of West Bengal, India. Issue 2 (12th November 2019) - Chatterjee, Debolina; Chopra Chatterjee, Suhita; Bhattacharyya, Tulika
Abstract : Purpose: Self-care is defined as the ability to take care of one's body and health with or without the help of healthcare personnel. The purpose of this paper is to explore the opportunities for self-care among imprisoned women within the constraints of a confined life, which, in turn, affect their health. Design/methodology/approach: Primary data have been collected through semi-structured interviews with 90 women in three prisons in the Indian state of West Bengal. Findings: Findings reveal that a majority of the women cited the inability to self-care was due to factors such as constricted architecture, specific penal policies that thwarted relational contexts in prisons and also the loss of control over their consumptive choices. However, it was found that coping mechanisms also existed among some women who actively constituted penal spaces for self-care. Many long-term imprisoned women tried to actively engage themselves in daily activities such as the "labour" allotted to them. Practical implications: The paper concludes that abilities to self-care have a deep impact on the health of women, which if not facilitated will lead to a health depleting experience. At a time when Indian prisons are focussing on rehabilitation, the recommendations for providing opportunities for self-care in prisons can minimize the "pains" of imprisonment and pave the way for rehabilitation. Originality/value: The research is based on data collected during original fieldwork conducted in three prisons in West Bengal, India. It provides valuable insights on how penal environments affect self-care opportunities of imprisoned women.